Influence of Pollination on Smut Disease and Yield in Maize - Mehmet Aydoğdu; Nuh Boyraz (Journal of Agricultural Sciences)
Ustilago maydis, causal agent of smut disease in maize, induces significant yield losses by forming colossal galls (tumours) on cobs. Since infection process of U. maydis is parallel with natural pollination of maize, an interaction between maize pollination and the smut fungus is probable. To reveal this interaction perceptibly, a 2-year field study was carried out in Antalya province of Turkey. As host plants, 8-maize-cultivars belonging to different maize variety groups [dent (Ada-523, Pioneer-3394 and Side), flint (Karaçay and Karadeniz Yıldızı), sweet (Merit and Vega) and popcorn (Antcin-98)] were used in the experiment. Inoculations were performed by injecting inoculum into cob silks in pre- and post-pollination periods in plots. In addition, control plots were set up for each treatment. In conclusion, average disease severity, incidence and yield losses of all the maize cultivars in pre-pollination inoculations (PrePI) were 3.8, 20.7 and 45.5%, whereas in post-pollination (PostPI) inoculations, they were 0.9, 15.7 and 35.9%, respectively. It was found that in both years, disease values of the PrePI were higher than those of the PostPI. This study suggested that pollination period of maize is an important factor affecting U. maydis infection in cobs and accordingly yield losses.